Название - IG Budaeva; EG Ovsyannikova; EN Goryunova; OV Kulemina; DV Zaitsev; DV Motorin; RSh Badaev; DB Zammoeva; VV Ivanov; KV Bogdanov; OS Pisotskaya; YuV Mirolyubova; et al. (Клиническая онкогематология)

(untitled)
Aim. To assess the efficacy of FLAG/FLAG-Ida regimen and to identify factors that influence remission, duration of disease-free survival (DFS) and overall survival (OS) of patients with relapsed/refractory acute myeloid leukemia (AML).